Antimicrobial Effect of the Triterpene 3β, 6β, 16β-Trihydroxylup-20(29)-ene on Planktonic Cells and Biofilms from Gram Positive and Gram Negative Bacteria. (29th June 2014) - Evaristo, Francisco Flávio Vasconcelos; Albuquerque, Maria Rose Jane R.; dos Santos, Hélcio Silva; Bandeira, Paulo Nogueira; Ávila, Fábio do Nascimento; da Silva, Bruno Rocha; Vasconcelos, Ariana Azevedo; Rabelo, Érica de Menezes; Nascimento-Neto, Luiz Gonzaga; Arruda, Francisco Vassiliepe Sousa; Vasconcelos, Mayron Alves; Carneiro, Victor Alves; et al.
Abstract : This study evaluated the antimicrobial effect of 3 β, 6 β, 16 β -trihydroxylup-20(29)-ene (CLF1), a triterpene isolated from Combretum leprosum Mart., in inhibiting the planktonic growth and biofilms of Gram positive bacteria Streptococcus mutans and S. mitis . The antimicrobial activity was assessed by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The antibiofilm potential was determined by quantifying total biomass and enumerating biofilm-entrapped viable bacteria. In addition, the acute toxicity of CLF1 on Artemia sp. nauplii was also determined. The results showed that CLF1 was able in inhibiting the growth of S. mutans and S. mitis with MIC and MBC of 7.8  μ g/mL and 15.6  μ g/mL, respectively. CLF1 was highly effective on biofilms of both bacteria. Only 7.8  μ g/mL CLF1 was enough to inhibit by 97% and 90% biomass production of S. mutans and S. mitis, respectively. On the other hand, such effects were not evident on Gram negative Pseudomonas aeruginosa and Klebsiella oxytoca . The toxicity tests showed that the LC50 of CLF1 was 98.19  μ g/mL. Therefore, CLF1 isolated from C. leprosum may constitute an important natural agent for the development of new therapies for caries and other infectious diseases caused by S. mutans and S. mitis .